2014
DOI: 10.1186/2162-3619-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression pattern of miR-29a, miR-29b and the target genes in myeloid leukemia

Abstract: ObjectivesThe miR-29 family have been demonstrated acting as vital tumor suppressor in multiple cancers as well as regulators in the adaptive immune system. Little is known about their role in leukemogenesis. The purpose of this study is to analyze the expression pattern of miR-29a/29b and its target genes Mcl-1 (myeloid cell leukemia sequence 1) and B-cell lymphoma 2 (Bcl-2) in myeloid leukemia.MethodsQuantitative real-time PCR was used for detecting genes expression level in peripheral blood mononuclear cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 48 publications
1
42
0
1
Order By: Relevance
“…We observed that there is a significant downregulation of mir29a-3p and mir92a-3p in the bone marrow aspirates and the plasma of the newly diagnosed AML patients when compared to normal subjects; (p <0.001). Similar Results were reported by other study groups (Zhu et al, 2013;Gong et al, 2014;Xu et al, 2014) who reported a downregulation in miR-29a/29b levels in peripheral blood mononuclear cells and bone marrow from AML patients compared with healthy individuals. Also, miR-29a was found to be downregulated in many other types of neoplasms like lung cancer (Barkley and Santocanale, 2013), oral squamous carcinoma (Lu et al, 2014), glioblastoma (Xi et al, 2017), metastatic prostate cancer (Ahmed et al, 2013), ALK-positive anaplastic large cell lymphomas (Desjobert et al, 2011), endocrine-sensitive breast cancer (Muluhngwi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that there is a significant downregulation of mir29a-3p and mir92a-3p in the bone marrow aspirates and the plasma of the newly diagnosed AML patients when compared to normal subjects; (p <0.001). Similar Results were reported by other study groups (Zhu et al, 2013;Gong et al, 2014;Xu et al, 2014) who reported a downregulation in miR-29a/29b levels in peripheral blood mononuclear cells and bone marrow from AML patients compared with healthy individuals. Also, miR-29a was found to be downregulated in many other types of neoplasms like lung cancer (Barkley and Santocanale, 2013), oral squamous carcinoma (Lu et al, 2014), glioblastoma (Xi et al, 2017), metastatic prostate cancer (Ahmed et al, 2013), ALK-positive anaplastic large cell lymphomas (Desjobert et al, 2011), endocrine-sensitive breast cancer (Muluhngwi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In case of miR-29, this microRNA family may target many transcription factors and anti-apoptotic genes (Si et al, 2013). Myeloid cell leukemia sequence1 (MCL1) has been identified as a potent target gene of miR-29a and miR-92a (Xu et al, 2014). Mcl-1 belongs to Bcl-2 family which considered an important player in regulation of apoptosis and any change in their expression levels will lead to the progression of human cancer (Thomas et al, 2010;Kadia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of miR-126 in acute myeloid leukemia (AML) patients associated with poor survival, and inhibition of miR-126 eradicates the CD34 + 38 À stem/progenitor cells in AML Tumor suppressor Upregulated [39,40,41] target sites were further studied according to the PCT values from the TARGETSCAN version 5.1. The target genes are involved in signaling pathways such as MAP kinase, transforming growth factor b, TP53 (p53), ErbB, and RUNX1, which are involved in HSC differentiation [42].…”
Section: Hsa-mir-20amentioning
confidence: 99%
“…miRNA-29b downregulates DNMT1 indirectly by targeting Sp1, a trans-activator of the DNMT1 gene due to a decrease in global DNA methylation and re-expression of p15 (INK4b) and ESR1. Moreover, miRNA-29 family members may downregulate the active DNA demethylation pathway members tet-methylcytosine dioxygenase (TET1) and thymine DNA glycosylase (TDG) [37,60]. miRNA-29 targets CCNT2 that is a component of the positive transcription elongation factor b (P-TEFb).…”
Section: Mirna-29mentioning
confidence: 99%